2010
DOI: 10.1038/sj.bjc.6605958
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 induces resistance to the anti-tumour effect of interferon-α/5-fluorouracil in hepatocellular carcinoma cells

Abstract: Background:We reported recently the clinical efficiency of interferon (IFN)-α/5-fluorouracil (5-FU) combination therapy in advanced hepatocellular carcinoma (HCC). However, prediction of the response to the combination therapy remains unsatisfactory. The aim of this study was to investigate the anti-tumour effects of microRNA (miR)-21 on the sensitivity of HCC cells to IFN-α/5-FU and whether miR-21 can be used as a predictor of the response to such therapy in HCC.Methods:Changes in the sensitivity of HCC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 43 publications
(67 reference statements)
6
130
1
Order By: Relevance
“…Previous measurements of miRNAs in liver samples revealed that let-7a, miR-16, miR-20, miR-21, and miR-22 were present at 700, 3 890, 130, 4 450, and 310 copies per cell, respectively [43], while miR-181a was expressed at 810 copies per cell in DP thymocytes [44] and miR-223 and miR-451 were 828 and 1 972 copies per cell in CD34(+)/CD133(−) cells [45]. It has been widely demonstrated that miRNAs expressed at these concentrations are biologically active [46][47][48][49]. We calculated the amount of MIR168a that was detected in 1 mg of total liver RNA.…”
Section: Ago2-associated Mature Mir168a In Mvs Is the Functional Formmentioning
confidence: 99%
“…Previous measurements of miRNAs in liver samples revealed that let-7a, miR-16, miR-20, miR-21, and miR-22 were present at 700, 3 890, 130, 4 450, and 310 copies per cell, respectively [43], while miR-181a was expressed at 810 copies per cell in DP thymocytes [44] and miR-223 and miR-451 were 828 and 1 972 copies per cell in CD34(+)/CD133(−) cells [45]. It has been widely demonstrated that miRNAs expressed at these concentrations are biologically active [46][47][48][49]. We calculated the amount of MIR168a that was detected in 1 mg of total liver RNA.…”
Section: Ago2-associated Mature Mir168a In Mvs Is the Functional Formmentioning
confidence: 99%
“…Another miRNA that has been shown to be involved in chemoresistance is miR-21. miR-21-transfected HCC cells are resistant to 5-fluorouracil/interferon-α [115] , which suggests that anti-miR-21 may increase the chemosensitivity of cancer cells. Indeed, anti-miR-21 improves the cytotoxicity induced by 5-FU in glioblastoma cells [116] .…”
Section: Implications Of Cell Cycle-related Mirnas In Anti-cancer Thementioning
confidence: 97%
“…These mechanisms lead to the stimulation of cell proliferation promoting migration and invasion. Tomimaru et al (2010) have demonstrated that miR-21 has an effect in the modulation of the response to IFN-␣/5-FU favoring the clinical response and survival. This miRNA is the first to be studied as a therapeutic tool and other two studies (Connolly et al, 2008;Zhu et al, 2011) have shown that the transfection of tumor cells with antisense oligonucleotides specific for mir-21 leads to a reduction of the cell growth and survival.…”
Section: Mir-21mentioning
confidence: 99%